Understanding the Challenges of Teaching Computer Science Subjects from School Teachers’ Perspective - Mahadzir, Nurul Husna; Abdul Razak, Nor Hafizah; Ismail, Siti Nurbaya; Idrus, Zanariah; Idrus, Zainura; Ramli, Roselina (UUM Press, 2024)
The implementation of Computer Science (CS) in Malaysian secondary schools aims to develop digital proficiency among youths. Despite this, Kedah state has seen fluctuating enrolment in CS elective subjects for the Sijil Pelajaran Malaysia (SPM) exam between 2018 and 2021, which contrasts with the increasing popularity of CS programs in higher education and the rising demand for CS skills. Addressing the challenges teachers face in delivering CS subjects is crucial, including issues like inadequate training, limited resources, language barriers, and diverse student backgrounds. This study uses a quantitative approach with self-developed questionnaires distributed among experienced CS teachers in Kedah to identify these challenges and propose solutions. Findings reveal a mix of experienced and less experienced teachers, mostly with medium-level proficiency. The study highlights difficulties in teaching Form 4 and Form 5 content and suggests improvements through professional development, collaboration, hands-on experiences, and updated resources to enhance teaching effectiveness and better align secondary education with higher education and job market needs.